2017
DOI: 10.1007/s11274-017-2240-7
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid production from submerged fermentation of broken rice using undefined mixed culture

Abstract: The present work aimed to characterize and optimize the submerged fermentation of broken rice for lactic acid (LA) production using undefined mixed culture from dewatered activated sludge. A microorganism with amylolytic activity, which also produces LA, Lactobacillus amylovorus, was used as a control to assess the extent of mixed culture on LA yield. Three level full factorial designs were performed to optimize and define the influence of fermentation temperature (20-50 °C), gelatinization time (30-60 min) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…Overall, the compositions of the tested starchy substrates are in agreement with those reported in the literature, and clearly confirmed that starch is the main polysaccharide in the selected substrates. Nunes et al and Favaro et al reported a starch content for broken rice of around 77%, with proteins between 7.5-8.5% [39,51]. Yokoi et al, analyzing the chemical composition of sweet potato waste, confirm a starch content of up to 50% [52].…”
Section: Starchy Waste Compositionmentioning
confidence: 96%
“…Overall, the compositions of the tested starchy substrates are in agreement with those reported in the literature, and clearly confirmed that starch is the main polysaccharide in the selected substrates. Nunes et al and Favaro et al reported a starch content for broken rice of around 77%, with proteins between 7.5-8.5% [39,51]. Yokoi et al, analyzing the chemical composition of sweet potato waste, confirm a starch content of up to 50% [52].…”
Section: Starchy Waste Compositionmentioning
confidence: 96%
“…Formulation of culture medium with mixtures of agro-industrial residues for fibrolytic enzymes production The SmF of selected microorganism was performed in Erlenmeyer flasks (250 ml, with 80 mL of medium described previously (section 2.2) during 288 h of incubation in a shaker at 28 ºC and 180 rpm. D-Optimal mixture design was performed in order to evaluate the effect of individual substrates and the interactions among them in ternary mixtures on xylanase and cellulase production (Fernández-Núñez et al, 2016;Nunes et al, 2017). The number of experimental combinations in each experimental design was enough to fit special cubic models for response variables.…”
Section: 3mentioning
confidence: 99%
“…For example, broken rice, one of the by‐products in rice milling, was converted directly to lactic acid by an undefined mixed culture without saccharification. Lactic acid production reached 9.76 g.L ‐1 , which was six times higher than that using pure culture . Potato peel waste (PPW), a byproduct generated in food‐processing plants, was also used for lactic acid production by using an undefined mixed culture .…”
Section: C3: Propionic Acid and Lactic Acidmentioning
confidence: 99%
“…Lactic acid production reached 9.76 g.L -1 , which was six times higher than that using pure culture. 18 Potato peel waste (PPW), a byproduct generated in food-processing plants, was also used for lactic acid production by using an undefined mixed culture. 19 Approximately 14.7 g.L -1 of lactic acid was produced in an airlocked glass bioreactor with a yield of 0.22 g.g -1 , when initial solid loading was 60 g.L -1 .…”
Section: Lactic Acidmentioning
confidence: 99%